Position Paper on School Guidance Services - 1980, Canadian School Trustees' Association (Canadian Journal of Counselling and Psychotherapy, 2012)
The problems currently faced by school guidance counsellors are defined and relevant recommendations for a meaningful role for guidance services in the school are articulated. Ways in which students can acquire knowledge of self, knowledge of the world, and life management skills are outlined. The roles of the counsellor, the teacher, the administrator, the school board, the parents, the community, and the Department of Education are stated and 12 recommendations for the improvement of guidance services are put forth.